مساهمة العدالة التنظيمية في تحقيق الرضا الوظيفي لدى العاملين في المؤسسة الاقتصادية - شروق, زوينة; خولة, سعيدي; نرجس, العمامرة (University of eloued جامعة الوادي, 2020)
The research aims to crystallize the concept of organizational justice and its role in achieving job satisfaction in the Algeria Telecom Corporation, a field study, and the importance of the research comes from the extent of its contribution to providing a valuable information base that helps to achieve job satisfaction, and to achieve the goal of this study, the hypotheses were selected by the spss statistical program to analyze The data where the results resulted in the acceptance of the research hypotheses, and the positive impression of the study sample about our subject was taken, and the study concluded that there is a role for organizational justice in achieving job satisfaction, and the research concluded the following results: Organizational justice includes three types, distributive justice, procedural justice, transactional justice, and job satisfaction is affected by many factors, including those related to the personality of the individual himself, including those related to the organizational environment. The study concluded that the degree of comprehension of the concepts of organizational justice and the concepts of job satisfaction was high. It also concluded that: Personal and functional variables do not affect the degree of organizational justice and job satisfaction in the institution يهدف البحث إلى بلورة مفهوم العدالة التنظيمية و دورها في تحقيق الرضا الوظيفي في مؤسسة إتصالات الجزائر دراسة ميدانية،وتأتي أهمية البحث من مدى مساهمته في تقديم قاعدة معلوماتية قيمة،تساعد على تحقيق الرضا الوظيفي،و لتحقيق هدف هذه الدراسة تم إختيار الفرضيات بواسطة البرنامج الإحصائي spssلتحليل البيانات حيث أسفرت النتائج عن قبول فرضيات البحث،و أخد إنطباع الإيجابي لدى عينة الدراسة حول موضوعنا و توصلت الدراسة إلى أنه يوجد دور للعدالة التنظيمية في تحقيق الرضا الوظيفي و خلص البحث إلى النتائج التالية:تشمل العدالة التنظيمية ثلاثة أنواع،العدالة التوزيعية،العدالة الإجرائية،العدالة التعاملية،كما يتأثر الرضا الوظيفي بالعديد من العوامل منها مايتعلق بشخصية الفرد ذاته،ومنها مايتعلق بالبيئة التنظيمية.و قد خلصت الدراسة إلى أن درجة إستيعاب مفاهيم العدالة التنظيمية ومفاهيم الرضا الوظيفي كانت مرتفعة.و خلصت أيضا إلى أن:لا تؤثر المتغيرات الشخصية و الوظيفية على درجة إستيعاب العدالة التنظيمية و الرضا الوظيفي في المؤسسة.
مذكرة ماستر ادارة اعمال
Keywords: العدالة - التنظيمية - الرضا; Justice - Organisationnel - Satisfaction